Snow conditions and usability value of pastureland for semi-domesticated reindeer (Rangifer tarandus tarandus) in northern boreal forest area - Kumpula, Jouko; Colpaert, Alfred (Rangifer, 2009)
We studied variation in snow conditions and selection of pasture area according to altitude by semi-domesticated reindeer (Rangifer tarandus tarandus) during 1999 - 2002 in a pine forest area utilised by forest industry in the Ivalo reindeer herding district, northern Finland. Snow conditions were measured over the course of three winters along equilateral triangles (side 3.5 km) for three times per winter. The altitudinal selection of pasture area by reindeer was studied using GPS tracking data (10 977 locations) from 29 female reindeer. We observed that interannual weather variation mostly affected the depth, density and hardness of snow in the study area. At the forest landscape level, snow depth and density increased with altitude. Thinnest and deepest snow cover occurred on western and northern slopes, respectively. In contrast, forest harvesting did not seem to affect snow conditions. From spring to autumn, reindeer mainly used higher altitudes in pastures. In early and mid-winter, when snow conditions were easy or moderate reindeer still preferred higher altitudes, but in late winter when snow conditions and food accession were at their most difficult, they preferred lower altitudes. We conclude that especially the use of high elevation forestland pastures may become more difficult for reindeer if the global climatic change causes higher winter precipitation to the northern boreal forest area. In general, the low-elevation forestland areas have primary winter grazing value for reindeer but these areas are also intensively used by forest industry.Abstract in Finnish / Tiivistelmä:Lumiolosuhteet ja laidunten käyttöarvo poronhoidossa pohjoisella havumetsäaluella Lumiolosuhteiden vaihtelua ja porojen (Rangifer tarandus tarandus) laidunalueen valintaa maaston korkeuden perusteella tutkittiin vuosina 1999–2002 metsätalouden hyödyntämällä mäntymetsäalueella Ivalon paliskunnassa, Pohjois-Suomessa. Lumiolosuhteet mitattiin kolme kertaa kunakin kolmena talvena käyttämällä mittaukseen tasasivuisia kolmioita (sivu 3,5 km). Porojen laidunalueen valintaa korkeusvyöhykkeen mukaan tutkittiin käyttämällä porojen GPS seurannan aineistoja 29 vaatimesta (yhteensä 10 977 paikannusta). Vuosien välinen säävaihtelu vaikutti eniten lumen paksuuteen, tiheyteen ja kovuuteen tutkitulla alueella. Maisematasolla lumen paksuus ja tiheys lisääntyivät alueen korkeuden kasvaessa metsämaalla. Ohuin lumikerros mitattiin länsirinteillä ja paksuin kerros pohjoisrinteillä. Sen sijaan metsien käsittelyllä ei näyttänyt olevan vaikutusta lumiolosuhteisiin. Keväästä syksyyn porot käyttivät pääosin ylemmillä korkeusvyöhykkeillä sijaitsevia laitumia. Alku ja keskitalvella, jolloin lumiolosuhteet olivat vielä verrattain helpot, porot suosivat edelleen ylemmille korkeusvyöhykkeille sijoittuvia laitumia, mutta lopputalvella lumiolosuhteiden ja ravinnonsaannin ollessa vaikeimmat, porot suosivat alempien korkeusvyöhykkeiden laitumia. On todennäköistä, että erityisesti ylemmillä korkeusvyöhykkeillä olevat metsämaan laitumet voivat tulla vaikeammaksi käyttää poroille talvella, mikäli ilmastonmuutos aiheuttaa talvisadannan lisääntymisen pohjoisella havumetsäalueella. Yleisesti alemmille korkeusvyöhykkeille sijoittuvilla metsämaan laidunalueilla on ensisijainen talvilaidunarvo poronhoidolle, mutta myös metsätalous hyödyntää näitä alueita intensiivisesti.Abstract in Norwegian / Sammendrag:Snøforhold og bruksverdi som beiteland for tamrein (Rangifer tarandus tarandus) i nordborale skogsområder I perioden 1999-2002 studerte vi tamreinens valg av beiteområder ettersnøforhold og høyde over havet i en furuskog utnyttet av skogsdriften i Ivalo reinbeitedistrikt nord i Finland. Snøforholdene ble målt 3 ganger per vinter i tre vintre etter likebeinte triangler med side 3,5 km. Reinens beiting i ulike høyder ble målt med GPS-sporing av 29 simler på tilsammen 10 977 observasjonspunkter. Vi observerte at værvariasjonen mellom år mest påvirket snødybde og snøens tetthet og hardhet. I skogslandskapet økte snødybden og tettheten med høydebeliggenheten. Tynnest og djupest snødekke fantes henholdsvis i vestlige og nordlige skråninger. Derimot syntes ikke skogsdriften å påvirke snøforholdene. Fra vår til høst utnyttet reinen hovedsakelig de høyestliggende beiteområdene. Tidlig og midt på vinteren når snøforholdene fortsatt var lette eller moderate, foretrakk reinen fortsatt høyereliggende beiter, men på seinvinteren når snøforholdene og plantetilgjengeligheten var på det vanskeligste, foretrakk reinen lavereliggende områder. Ut fra observasjonene kan vi antyde at særlig høyereliggende beiteområder blir mindre tilgjengelig for reinen om det blir økt vinternedbør i de nordlige skogsområdene som følge av globale klimaendringer. Vanligvis har de lavtliggende skogsområdene størst beiteverdi for reinen om vinteren, samtidig som disse områdene også er de mest intesivt utnyttede hogstområder for skogsindustrien.